ANALYSIS OF SOCIAL INTERACTION OF MENTALLY RETARDED CHILDREN - Yudhie Suchyadi; Yulia Ambarsari; Elly Sukmanasa (UNIVERSITAS PAKUAN, 2018)
Differences in the characteritics of children with special needs will require the ability of teachers to combine various abilities and talents of each child, such as mentally retarded children who need communication like children in general. His developmental delays are often excluded from his playing enviranment, thus the need for good social interaction with mentally retarded children. Based on these problems, a study was conducted to describe the findings of social interaction in mentally retarded children in extraordinary school Mentari Kita. The research is a descriptive analysis with qualitative research approach. Technique of data analysis was performed with data reduction stage, the presentation of data, and verification (conclusions). Researchers used the test of credibility, transferabilitas, dependabilitas, and konfirmabilitas to obtain the validity of the data. The result showed that the way social interaction with mental retardation children how do social contacts and communication as being able to respond when invited to communicate but it should be repeated over and over,the subject has a weakness in the concentration of so when invited to talk hard staring at your opponents interlocutor. When did the subject communication using language that sounds stilted. Social contact subject well againts his peers is characterized by sensitivity to her friends when in distress, want to help his friend like get a pencil, and divide the food per day taken by subject. Based on the above research result it can be concluded that the way the social interactions of the child with mental retardation how do social contacts and communication in accordance with the terms of the occurrence of social interaction. Keywords: Social Interaction, Mental Retardation